Declining radiation dose of coronary computed tomography angiography: German cardiac CT registry experience 2009-2014 - Schmermund, Axel; Korosoglou, Grigorios (Clinical research in cardiology, 2017)
Background: Coronary computed tomography angiography (CTA) is increasingly used as a test to rule out coronary artery disease (CAD) in patients with a low to intermediate pre-test probability of the disease. We used the database of the German CT registry, collected between 2009 and 2014 in a broad patient population, to analyze contemporary radiation dose associated with coronary CTA in clinical practice.Patients and methodsThe prospective observational registry included a total of 7061 patients ≥18 years, referred to 12 participating centers for a clinically indicated cardiac CT examination. All centers were cardiology units well experienced in CTA and used multi-slice CT scanners with at least 64 rows. Coronary CTA was performed in a subset of 5001 patients, 59.6 ± 11.8 years, body mass index (BMI) 26.9 ± 4.5 kg/m2, 38% females. Three time periods with approximately equal numbers of patients were created (01/09-03/10, 04/10-03/11, 04/11-07/14). The dose-length product of all examinations and derived effective dose in mSv (conversion factor k = 0.014) as well as the influence of patient characteristics on dose were compared for the three time periods.ResultsBMI and proportion of female patients remained stable over time, and mean heart rate decreased from 60.3 ± 9.0 to 58.5 ± 9.3 bpm from the first to the last time period (p < 0.001). Overall, the mean effective dose of coronary CTA was 3.6 mSv (Q1 1.8 mSv, Q3 7.4 mSv). Within the three time periods, it declined from 5.6 (2.7, 8.6) mSv during the first to 4.8 (2.1, 8.2) mSv during the second and 2.5 (1.3, 4.6) mSv during the last time period (p < 0.001). Paralleling the decline in radiation dose over time, the proportion of prospectively ECG-triggered examinations increased (68, 79, 83%; p < 0.001), and the proportion of examinations with retrospective gating and no tube current modulation decreased (5.3, 4.0, 1.6%; p < 0.001). Tube current (mAs) and voltage (kV) both decreased over time. In multivariable analysis, besides earlier time period, further independent predictors of an increased radiation dose were older age, higher heart rate, and higher BMI as well as the technical factors higher mAs, higher kV, and retrospective gating. At three sites, CT scanners with improved technology were installed during the last time period.ConclusionsIn current clinical practice among German cardiology units with specific expertise in cross-sectional cardiovascular imaging, overall radiation dose of coronary CTA was comparably low. Over time, a decline in radiation dose was demonstrated, probably due to a combination of improvements in data acquisition protocols and patient preparation as well as installation of new CT scanners with advanced technology.